Generative Design Conversion to Editable and Watertight Boundary Representation. (October 2019) - Marinov, Martin; Amagliani, Marco; Barback, Tristan; Flower, Jean; Barley, Stephen; Furuta, Suguru; Charrot, Peter; Henley, Iain; Santhanam, Nanda; Finnigan, G. Thomas; Meshkat, Siavash; Hallet, Justin; et al.
Abstract: We present the first, to our knowledge, fully automatic method for the conversion of a general generative design to a watertight B-Rep composed of the exact residual geometry of the input solids and editable T-NURCC surfaces. The design can be synthesized by any combination of both additive and subtractive in-synthesis processes, and constrained by any number of keep-in and -out solids. Our method requires only the input generative setup solids, rudimentary data from the solve, and a boundary mesh of the optimized design. Leveraging the generative solve data, we augment the boundary mesh with "incidence" attributes linking it to the input solids, and partition it into organic and incident regions. The organic regions are parameterized and approximated with T-NURCCs. Then, their boundaries are "pulled" into the adjacent input solids to construct clean intersection curves. Finally, the organic surfaces are combined with the input solids to compose a watertight solid B-Rep of the generative design. Without such an automatic conversion, users seeking to exploit generative designs in downstream workflows (e.g. setting up assembly constraints, simulation analyses, performing parametric edits) have to manually convert the design to a B-Rep, slowing down the path to manufacturing and increasing the product time to market. As a result of our work, engineers can now quickly obtain useful CAD models of any number of generative designs computed by a variety of algorithms, settings and iterations. Highlights: High-quality conversion method to obtain editable CAD models from generative designs. Combines exact residual geometry of the input solids and editable T-NURCC surfaces. Fully automatic algorithm produces watertight B-Reps. Any combination of additive and subtractive in-synthesis processes and constraints.